“Anyone Who’s Watching Can See That You’re Watching, Too”: A Case Study of Prosumption and Visibility Labours on Instagram Live - Jones, Corinne (Surveillance & Society, 2025)
Online audiences have become increasingly visible to each other. Recent work in Surveillance & Society has suggested that visible viewership in gaming constitutes “visibility labour” (Abidin 2016). Yet, little work has sketched the relationship between visible consumption, visibility labours, and social media’s surveillance economy. This article fills that gap by offering a preliminary structural outline of how visible consumers play a role in digital surveillance economies. I ask: What role does visible consumption play in digital surveillance economies on Instagram Live? What kinds of visibility labour are demanded of visible consumers, and with what effects? First, top-down surveillance of user interactions turns involuntarily visible consumers into social producers through metrified viewership and personal profiles. Second, lateral surveillance, such as moderator features and reporting tools, also turns voluntarily visible consumers into social producers by reproducing Instagram’s brand and deflecting from government oversight. In the context of Instagram Live, making users’ consumption habits socially public extends surveillance culture and neoliberal trends on social media, whereby market forces are extended into further reaches of social life.